Prophylaxis in real life scenarios. (May 2014) - Fischer, K.; Konkle, B.; Broderick, C.; Kessler, C. M.
Summary: Prophylaxis has become the standard mantra of care for those individuals with severe haemophilia A and B. Primary prophylaxis is advocated to prevent the occurrence of symptomatic acute spontaneous haemarthroses and to preserve joint structure and function. Typically, twice or thrice weekly infusions of factor VIII or IX concentrates are integral to this treatment approach. Secondary prophylaxis is initiated after the relentless cycle of progressive joint damage has been triggered by prior haemarthroses and is intended to preserve existing joint health by preventing additional spontaneous bleeding events. Event‐driven prophylaxis involves the administration of clotting factor concentrates to prevent acute traumatic bleeds, which are anticipated to occur in association with surgical or physical trauma. This regimen enhances the effectiveness of primary or secondary prophylaxis protocols or on‐demand approaches to replacement therapy. Besides the marked reduction in the so‐called annual bleed rate, prophylaxis regimens frequently increase personal self‐confidence to embark on a more active and physical lifestyle; however, in reality, prophylaxis must be individualized in accordance with bleeding phenotypes, with the unique pharmacokinetic profile of administered replacement clotting factor concentrates, with the specific clinical scenario, and with the degree of intensity anticipated for any physical activity. The introduction of extended half‐life replacement products will also influence how these prophylaxis regimens will be accomplished. The following scenarios will discuss how prophylaxis regimens can be implemented to protect the individual from developing spontaneous and activity‐induced acute bleeding complications and to maintain an improved quality of life.